Court Reform - Bedner, Adriaan (Law, Governance, and Development, 2008)
Three types of strategies have been common for court reform programmes: the 'holistic', the 'tactical', and the 'strategic' approach. This Research and Policy Note discusses strategic court reform and its underlying ideas. Its main intention is to alert those involved in judicial reform to some of the pitfalls and choices connected to particular types of interventions. The concluding remarks will comment on the political nature of judicial reform and on a model to design a proper sequence of interventions for judicial reform.